Evolutionary response to climate change in migratory pied flycatchers - Helm, B; Van Doren, B; Hoffman, D; Hoffman, U (Cell Press, 2019)
Climate change is rapidly advancing spring phenology but at different rates in different species. Whether these advances are solely driven by phenotypic plasticity or also involve evolution is hotly debated. In some species, including avian long-distance migrants, plastic responses to early springs may be constrained by inherited circannual timing programs, making evolutionary adjustment the only viable mechanism for keeping pace with shifting phenology. This constraint may be contributing to population declines in migratory species. To test whether a migrant’s timing program has evolved, we replicated an experimental study of the annual cycle of long-distance migratory pied flycatchers (Ficedula hypoleuca) after 21 years of warming. Flycatchers are a model for studying constrained ecological responses to climate change. We show that the phase of the flycatcher circannual clock controlling spring moult, migration, and reproductive timing advanced by 9 days. A nearby wild population mirrored these changes, concurrently advancing egg-laying by 11 days. Furthermore, the time window during which wild flycatcher reproductive timing was most sensitive to ambient temperature advanced by 0.8 days year–1. These results support a role of phenotypic evolution in changing spring phenology. We suggest that the timing programs of long-distance migratory birds may have greater adaptive potential than previously thought, leaving some scope for evolutionary rescue in a changing climate.